Comparative Effectiveness of Combination Therapy in Patients with Chronic Kidney Disease and Diabetes mellitus Type 2 using Real World Data - Janis Casper; Julian Doricic; Zhejia Tian; Jonas Michael Willerding; Marit Glammeier; Anette Melk; Kai Schmidt-Ott; Bernhard M W Schmidt (Nephrology Dialysis Transplantation, 2026)
Abstract Background and hypothesis Diabetes mellitus type 2 (T2DM) is the primary driver of chronic kidney disease (CKD). Renin-angiotensin-aldosterone system inhibitors (RAASi) represent basic therapy for CKD in T2DM. Recent studies demonstrated renal benefits of sodium glucose cotransporter 2 inhibitors (SGLT-2i) and glucagon-like peptide-1 receptor agonists (GLP1-RA), but data on direct comparisons and potential additive effects of their combination remain unclear. Methods Using data from the US Collaborative Network in TriNetX, we analyzed patients with T2DM, CKD, and eGFR between 20-60 mL/min. A target-trial emulation with propensity score matching evaluated different drug combinations in first-user design versus RAASi monotherapy. Primary endpoint was all-cause mortality. Secondary outcomes included a composite endpoint of all-cause mortality and major adverse kidney events (MAKE), and MAKE as a distinct endpoint. MAKE was defined as CKD stage 5, end-stage renal disease, eGFR <15 mL/min, or need for renal replacement therapy. Kaplan-Meier analysis was used for survival analysis. Results We identified n= 19,139 patients with T2DM, an eGFR between 20-60mL/min and already established RAASi treatment. RAASi combined with SGLT-2i (aHR 0.602, 95% CI 0.528–0.686) or GLP1-RA (aHR 0.597, 95% CI 0.507–0.702) reduced mortality compared to RAASi monotherapy. Triple therapy showed the greatest mortality reduction (aHR 0.317, 95% CI 0.234–0.429). Secondary endpoints favored dual therapy over RAASi monotherapy, with triple therapy providing the strongest risk reduction for both composite endpoint (aHR 0.414, 95% CI 0.328–0.524) and MAKE (aHR 0.509, 95% CI 0.374–0.693). Conclusion SGLT-2i and GLP1-RA independently improve outcomes in T2DM patients on RAASi treatment. Triple therapy was associated with lower risk for mortality and renal outcomes.